MANIFESTATION OF ROMANTICISM IDEOLOGY IN LEILA S. CHUDORI'S PULANG - Yuani Nurdwi Kaesari (Saksama, 2022)
This article aims to analyze the elements of romanticism ideology in the novel entitled Pulang by Leila S. Chudori. Pulang was published in 2012 with the genre of historical fiction. Romanticism is an ideology in which prioritizes feelings and imagination. The theory used in this article is romanticism ideology by William Wordsworth on one of his books Preface to the Second Edition of Lyrical Ballads. Based on the analysis conducted towards the narratives within the novel, it can be found several elements of romanticism which expressed by the author through the description of nature and the portrayal of the characters.